Sāngalī yethẽ Śake 1841 madhyẽ jhālelyā Jyotisha-Sammelanācā ahavāla (Pa. Pra. Kameṭī, 1920)
Proceedings of the 3rd Seminar on Hindu astrology organized by Jyotishasammelana va Pañcāṅgapravartana Kameṭī